EFEKTIFITAS MODEL PROBLEM BASED LEARNING BERBASIS MEDIA DIGITAL UNTUK MENINGKATKAN MOTIVASI BELAJAR IPAS SISWA KELAS IV SDN TEGOWANUH - Diah Retno Wati; Heri Maria Zulfiati; Daimul Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effectiveness of Problem Based Learning (PBL) model based on digital media in increasing the learning motivation of fourth grade students of SDN Tegowanuh. This research was conducted in two cycles, with each cycle consisting of four stages: planning, action, observation, and reflection. The subjects of the study were fourth grade students of SDN Tegowanuh, totaling 17 students. Data on students' IPAS learning motivation were collected through questionnaires. The data analysis technique used was descriptive statistics. Based on the results of data analysis, in cycle I, the average student's science learning motivation after participating in learning by applying the digital media-based Problem Based Learning learning model was 140 and was in the high category. The percentage of classical completeness is 82%. In cycle II, the average learning motivation of IPAS students increased to 150 and was in the very high category. The percentage of classical completeness is 94%. This shows that the PBL model based on digital media is effective in increasing the learning motivation of fourth grade students of SDN Tegowanuh.